Changes in Serum Mineral Markers in Menopausal Women (Advancements in Homeopathic Research, 2022)
Menopause is the transition phase of a women’s life and of vital significan0ce where several changes occur in the whole body including the serum mineral levels. Various symptoms and signs are seen to accompany this transition period. Knowledge of changes of internal bio mineral markers will not only enhance our knowledge but also will help in providing essential management during this phase of a women’s life
Keywords: menopause; serum calcium; serum magnesium; serum copper; serum phosphates; serum ferritin; trace elements